Activities of daily living in patients with chronic obstructive pulmonary disease with depressive symptoms - Rilda Carla Alves de Souza; Fabíola Cássia de Oliveira Silva Vieira; Graziella Monicky Oliveira Costa; Kamila Roberta Perpétua de Souza; Laura Maria Gomes de Siqueira; Patrícia Érika de Melo Marinho (Universidade de São Paulo, 2020)
ABSTRACT This cross-sectional study assessed the activities of daily living (ADL) and risk factors for developing depressive symptoms in patients with chronic obstructive pulmonary disease (COPD) and was carried out at the pulmonology outpatient clinic of the Hospital Universitário Oswaldo Cruz. Two hundred two (202) patients with COPD participated in the study. We evaluated the sociodemographic and anthropometric data, the ADL by means of Pulmonary Functional Status and Dyspnea Questionnaire - Modified version (PFSDQ-M), and the presence of depressive symptoms using the Beck Depression Inventory (BDI). All domains (dyspnea, fatigue and activity changes) of PFSDQ are compromised in patients with depressive symptoms. The prevalence of depressive symptoms was 38.6%. The chance of developing these symptoms was higher for those who used more than one bronchodilator (OR: 2.82, CI 95%: 1.47-5.38, p=0.002), presented dyslipidemias (OR: 2.74, CI95%: 1.24-6.07, p=0.012), had a heart disease (OR: 2.82, CI 95%: 1.18-6.74, p=0.020), presented expectoration (OR: 2.44, CI 95%: 1.2-4.95, p=0.014) or did not have a partner (OR: 2.58, CI 95%: 1.36-4.9, p=0.004). COPD patients with depressive symptoms had all domains of ADL compromised compared to patients without these symptoms.